Digital rights management in consumer electronics products. - Jonker, W. (IEEE Signal processing magazine)
In the current consumer electronics (CE) environment, we see many activities in content protection and digital rights management (DRM) which could lead to a situation with many standards and unnecessary limitations on the flow of content over various devices. As a result, the main challenge in the CE environment is to develop DRM solutions that allow interacceptable exchange of content that is acquired via any of the main distribution channels to the customer, being discs media, broadband, broadcast, and wireless. To achieve this, several important architectural and research issues have to be resolved. These solutions can only emerge through tight cooperation between the stakeholders and through the development of open standards.